Влияние вариаций ротационного режима Земли и лунно-солнечных приливов на напряженное состояние тектоносферы - Довбнич, М.М. (Видавничий дім "Академперіодика" НАН України, 2007)
A technique and results of the estimation of the stress state of the tectonosphere produced by variations of the rotational regime and the lunar-solar influence are considered. The quantitative characteristics of the stress produced by cosmogonic factors are given.